Pengaruh Penerapan Pemeriksaan Pajak dan Pelaporan Pajak Secara Online Terhadap Tingkat Kepatuhan Pelaporan Wajib Pajak Orang Pribadi Pada KPP Pratama Pamekasan - Achmarul fajar; Runik Puji Rahayu (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Timor, 2022)
In achieving the level of compliance of the Individual Taxpayer, it is necessary to evaluate the public awareness to comply with the rules that apply as a Taxpayer, at this time the Taxpayer has been introduced to e-filing which with all the conveniences and benefits offered to support the level of compliance of taxpayers' reporting. The purpose of this study was to determine the impact of applying online tax reporting or e-filing to the level of compliance of Individual Taxpayer reporting at the Pamekasan Primary Tax Service Office. The theory used in this study, namely the impact and satisfaction of the use of e-filing, and the factors that affect taxpayer compliance. While the type of research used is qualitative research using data tabulation techniques obtained. While the data source used in this study uses primary data and secondary data. The results of this study indicate that the application of online reporting or e-filing is sufficient to have a good impact on Individual Taxpayers and Pamekasan Taxpayers in improving tax reporting compliance through e-filing. The number of tax reporters through e-filing is increasing, it's just that there is a need for an evaluation of system performance and detailed guidance information so that users are more comfortable and understanding when using e-filing, so that more Taxpayers will use e-filing.